2003
DOI: 10.1063/1.1584786
|View full text |Cite|
|
Sign up to set email alerts
|

Vertical channel all-organic thin-film transistors

Abstract: Articles you may be interested inAll-organic thin-film transistors made of poly(3-butylthiophene) semiconducting and various polymeric insulating layers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…Using the latter route, artificial thin film structures have been obtained for growth of hexabenzocoronene 6 on metal surfaces revealing a cofacial -stacking of the planar molecules which is of great interest for the fabrication of vertical thin-film OFET structures. 7 In view of these considerations, recent scanning tunneling microscopy (STM) results 8 reported by Kang and Zhu have attracted some attention. From the STM data, it was concluded that on Au substrates, organic molecular-beam deposition (OMBD) of pentacene leads to the growth of thin pentacene adlayers with a structure different from that of the bulk, namely with all molecular planes orientated parallel to the substrate.…”
mentioning
confidence: 99%
“…Using the latter route, artificial thin film structures have been obtained for growth of hexabenzocoronene 6 on metal surfaces revealing a cofacial -stacking of the planar molecules which is of great interest for the fabrication of vertical thin-film OFET structures. 7 In view of these considerations, recent scanning tunneling microscopy (STM) results 8 reported by Kang and Zhu have attracted some attention. From the STM data, it was concluded that on Au substrates, organic molecular-beam deposition (OMBD) of pentacene leads to the growth of thin pentacene adlayers with a structure different from that of the bulk, namely with all molecular planes orientated parallel to the substrate.…”
mentioning
confidence: 99%
“…4,5 Some approaches to enhance the OFETs' performance, such as decreasing the channel length and increasing the dielectric constant of the gate dielectrics, have been reported. [6][7][8][9][10][11] However, the performance is still quite limited. In this letter, we demonstrate an organic field effect transistor that utilizes a vertically stacked structure with promising performance.…”
mentioning
confidence: 99%
“…͑1͒, mobility is estimated to be 0.30 cm 2 / V s, which is still less than the typical value ϳ1.0 cm 2 / V s for the lateral devices prepared at the same time for a reference. It is to be emphasized that the achieved on-off ratio is outstanding as compared with various vertical OFETs reported previously, [13][14][15] in which the ratios are less than ϳ10 4 . As compared with these vertical transistors, the present 3D-OFETs are reproducing more ideal vertical MIS structure, in which the semiconductor channel and the gate electrode are facing well with each other and the source and the drain electrodes are explicitly separated by the semiconductor.…”
mentioning
confidence: 86%